Modification of potato starch with adipic acid and research of modification product as raw materials for food biodegradable packaging - Shulga, Sergii; Shulga, Oksana; Simurova, Natalia (My University, 2021)
The aim of our work was to study the modification of potato starch with adipic acid chloride in order to further physicochemical study of the obtained product and use, for example, as an effective film former of biodegradable films/coatings. The modified product has a number of different characteristics from the original product. The use of starch as a natural substance that is capable of biodegradation makes it possible to is recommend the resulting product as a raw material for environmentally friendly packaging materials.

Метою роботи було проведення модифікації картопляного крохмалю хлоридом адипінової кислоти з метою подальшого фізико-хімічного дослідження отриманого продукту та використання його, наприклад, як ефективного плівкоутворювача біодеградабельних плівок/покриттів. На підставі ряду досліджень визначено, що модифікований продукт має ряд відмінних характеристик від вихідного продукту. Крім того, використання крохмалю як природної речовини, яка здатна до біодеструкції дає можливість рекомендувати отриманий продукт як сировину для екологічних пакувальних матеріалів.
Keywords: кафедра експертизи харчових продуктів; adipic acid; packaging; ecological; biodegradable; кафедра харчової хімії; крохмаль картопляний; кислота адипінова; упаковка; біодеградабельна упаковка